PENGAWETAN TUJUH BELAS JENIS KAYU SECARA RENDAMAN DINGIN DENGAN BAHAN PENGAWET BFCA (Cold Soaking Treatment of Seventeen Wood Species Using BFCA Preservative) - Sasa Abdurrohim; Barty Barty (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Wood samples of 17 species measuring 5 cm x 5 cm x 30 cm were treated with BFCA preservative by cold soaking treatment were 1, 3 and 5 days with preservative concentration of 5 and 10 percent.Taking retention and penetration requirements into consideration for wood uses under roof and in the Open air, both .Without ground contact, the resulls that seven wood species could be satisfactorily treated under the experimental conditions. However, it is important to note that three of the seven species, i.e. tumbawa (Dysoxylum sp.), cempaka (Ehmerilla ovalis) and merawan (Hopeasp.) falfilled only the requirements for wood usage under the roof without ground contact. The treatment schedule proposed for the seven wood species is also presented in this paper.